Philosopher gone wild' wins theology prize: $1.1 million award honors innovators in the study of religion and spirituality - Rivera, John, author; Baltimore Sun Media Group, publisher (Colorado State University. Libraries, 2003)
Holmes Rolston, III, philosopher, naturalist and self-described "philosopher gone wild," has won the 2003 Templeton Prize. Rolston pioneered the study of environmental ethics. He has been charged by an elephant and once stared down a leopard in Africa. Rolston has quarreled with both science and religion about values in nature. He recounts a religious experience experiencing the Pasqueflower blossoming in the snow after winter in the Rockies.
Keywords: philosophy professor; Colorado State University; Templeton Prize; Rolston, Holmes, 1932-2025